2021
DOI: 10.1111/brv.12791
|View full text |Cite
|
Sign up to set email alerts
|

The naked truth: a comprehensive clarification and classification of current ‘myths’ in naked mole‐rat biology

Abstract: The naked mole‐rat (Heterocephalus glaber) has fascinated zoologists for at least half a century. It has also generated considerable biomedical interest not only because of its extraordinary longevity, but also because of unusual protective features (e.g. its tolerance of variable oxygen availability), which may be pertinent to several human disease states, including ischemia/reperfusion injury and neurodegeneration. A recent article entitled ‘Surprisingly long survival of premature conclusions about naked mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 230 publications
(345 reference statements)
0
68
0
Order By: Relevance
“…We speculate that the evolution of long-lived mammals may have provided an example of tuning the effective temperature. Naked mole rats are known for their exceptional stress resistance, DNA repair efficacy [44][45][46][47], and translational fidelity [48,49]. Both factors should reduce the noise in the regulatory circuits and lower the effective temperature of the system.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the evolution of long-lived mammals may have provided an example of tuning the effective temperature. Naked mole rats are known for their exceptional stress resistance, DNA repair efficacy [44][45][46][47], and translational fidelity [48,49]. Both factors should reduce the noise in the regulatory circuits and lower the effective temperature of the system.…”
Section: Discussionmentioning
confidence: 99%
“…The NMR lifespan is fivefold greater than that predicted allometrically based on its body size 2 . This extreme longevity of NMRs is accompanied by a nonincreasing mortality rate that led to the conclusion that the NMR is a non-aging mammal [6][7][8] . Although the lack of demographic aging is most confidently revealed up to the age of 12 years (because the vast majority of examined animals were within this age range) 6,9 , this age span is two times longer than the lifespan expected based on body size and 20-fold longer than the possible onset of reproduction 7 .…”
mentioning
confidence: 99%
“…Although the lack of demographic aging is most confidently revealed up to the age of 12 years (because the vast majority of examined animals were within this age range) 6,9 , this age span is two times longer than the lifespan expected based on body size and 20-fold longer than the possible onset of reproduction 7 . The NMR was shown to resist age-related diseases such as cancer and cardiovascular disease [10][11][12] , shows no change in body composition and metabolic profiles with age 13 , and in general, its observed health deterioration (e.g., cataracts and osteoarthritis) do not appear to change in severity or frequency as age increases 8 . However, NMRs do exhibit age-related changes, such as decreased activity and altered (lighter and parchment-like) skin 1,2,5 .…”
mentioning
confidence: 99%
“…Interestingly, the miRNA involvement in responses to hypoxia have been studied and many oxygen-responsive miRNAs (OxyMiRs) on major metabolic pathways were identified. Hypoxia is also one primary cause of tumor induction in some forms of the cancers [ 65 , 66 ]. An international collaborative study from our lab explored the hypoxia-induced miRNA responses in the brain of naked mole rats and showed that many differentially expressed miRNAs were involved in neuroprotection and anti-apoptotic responses [ 67 ].…”
Section: Microrna Biology From Extreme Animal Survivalists To Human Health and Diseasementioning
confidence: 99%